A multi-professional educational intervention to improve and sustain respondents' confidence to deliver palliative care: A mixed-methods study. (February 2018) - Reed, Elizabeth; Todd, Jennifer; Lawton, Sally; Grant, Robert; Sadler, Clair; Berg, Jane; Lucas, Caroline; Watson, Max
Background: Education has been highlighted as fundamental in equipping healthcare professionals with essential knowledge and skills to provide good end-of-life care. Multiprofessional educational programmes have a positive influence on knowledge, attitude and confidence but few have sought to understand the longer term impact on care delivery. The European Certificate in Essential Palliative Care is an 8-week home-study-based programme for healthcare professionals and is currently run in nine centres. Successful candidates have undertaken the course from their own countries around the world. This article describes the evaluation of the European Certificate in Essential Palliative Care which has been evolving over 15 years. Aims: To evaluate the impact an educational intervention has on participants' confidence in palliative care, to determine whether this is sustained over time and explore participants' perception of the influence of the course on confidence. Design: A mixed-method longitudinal approach. Setting/participants: A survey using a self-efficacy scale was emailed to 342 candidates who received an educational intervention and semi-structured interviews to a sub-sample of 15 candidates at baseline, 3 and 6 months. Results: At 3 months, candidates had almost 20 times higher odds of being above any given level of confidence than at baseline which was sustained at 6 months. Qualitative analysis identified examples of increased competence and confidence improving palliative care delivery. Conclusion: Findings suggest that the European Certificate in Essential Palliative Care improves confidence in palliative care and that this is sustained over time with evidence of confidence in symptom control, communication and a holistic approach in clinical practice.